Does police work need a police institution? The evidence from Mogadishu. (18th May 2016) - Hills, Alice
Abstract : What happens to the organisation and activity of public policing when the institutions and processes on which it is seemingly predicated for existence and opportunity fragment? This article uses the experience of a paradigmatically weak police force – in this case, Mogadishu's Somali Police Force (SPF) – to question two aspects of police studies orthodoxy: that (1) police work is dependent on a police institution and (2) discipline and formality are key to structuring and understanding everyday police work. The SPF's record shows that the critical variables affecting police work are security levels, legacy issues and functional skills, rather than institutional resources, discipline or formality. Institutional resources are desirable, but do not necessarily play a significant role in influencing, co-ordinating or regulating officers' behaviour or goals, while the discipline and formality associated with ranks and uniforms are optional, rather than essential. The SPF's experience is extreme, yet the insight it offers into the relative importance of institutional resources, hierarchy and discipline for everyday police work has analytical and empirical implications for police studies more broadly.